Peramalan Tingkat Penghunian Kamar Hotel Bintang Lima Provinsi Bali Menggunakan Metode ARIMA dan Fuzzy Time Series Lee - Rahayu Dwiastuti Pujiningrum; Sulistijanti, Wellie (Universitas Mataram, 2024)
This research focuses on forecasting the Occupancy Rate of five-star hotels in the Province of Bali. The increase in Occupancy Rate directly impacts the increase in the number of hotel rooms, which is a key factor for Bali Province as a leading tourist destination in Indonesia and globally. The data used spans from November 2021 to November 2023, with the methods employed being ARIMA with a model of (1,1,1) and Fuzzy Time Series Lee. After conducting the research, the accuracy of the forecast is evaluated through Mean Absolute Percentage Error (MAPE). The MAPE for ARIMA (1,1,1) is found to be 71.4413, while the Fuzzy Time Series Lee method yields a MAPE of 1.1778. With a significantly lower MAPE, the Fuzzy Time Series Lee method is considered more accurate in forecasting the Occupancy Rate of five-star hotels in the Province of Bali for the December 2023 period, with a forecast result of 70.4033%.